Deficiency of the sphingosine‐1‐phosphate lyase SGPL1 is associated with congenital nephrotic syndrome and congenital adrenal calcifications. Issue 4 (6th March 2017) - Janecke, Andreas R.; Xu, Ruijuan; Steichen‐Gersdorf, Elisabeth; Waldegger, Siegfried; Entenmann, Andreas; Giner, Thomas; Krainer, Iris; Huber, Lukas A; Hess, Michael W; Frishberg, Yaacov; Barash, Hila; Tzur, Shay; et al.
Abstract : Sphingosine‐1‐phosphate (SiP) is an intra and extracellular signaling molecule involved in angiogenesis, vascular maturation, and immunity. SiP is irreversibly degraded by sphingosine‐1‐phosphate lyase 1, encoded by SGPL1 . Abstract: We identified two unrelated consanguineous families with three children affected by the rare association of congenital nephrotic syndrome (CNS) diagnosed in the first days of life, of hypogonadism, and of prenatally detected adrenal calcifications, associated with congenital adrenal insufficiency in one case. Using exome sequencing and targeted Sanger sequencing, two homozygous truncating mutations, c.1513C>T (p.Arg505*) and c.934delC (p.Leu312Phefs*30), were identified in SGPL1 ‐encoding sphingosine‐1‐phosphate (S1P) lyase 1. SGPL1 catalyzes the irreversible degradation of endogenous and dietary S1P, the final step of sphingolipid catabolism, and of other phosphorylated long‐chain bases. S1P is an intracellular and extracellular signaling molecule involved in angiogenesis, vascular maturation, and immunity. The levels of SGPL1 substrates, S1P, and sphingosine were markedly increased in the patients' blood and fibroblasts, as determined by liquid chromatography–tandem mass spectrometry. Vascular alterations were present in a patient's renal biopsy, in line with changes seen in Sgpl1 knockout mice that are compatible with a developmental defect in vascular maturation. In conclusion, loss of SGPL1 function is associated with CNS, adrenal calcifications, and hypogonadism.